Investigation of the activity of sulfonamide anti-bacterial drugs in Mycobacterium tuberculosis and the role of oxidative stress on the efficacy of these drugs - Macingwana, Lubabalo (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.